Case Report: Systemic Amyloidosis Involving the Heart and Skeletal Muscle - Lv, Pinchao; Li, Yuxi; Wu, Lin; Shi, Qiuping; Meng, Lingchao; Yu, Xiaojuan; Nong, Lin; Li, Jianping (Frontiers in Cardiovascular Medicine, 2022)
Background Amyloidosis refers to an etiologically heterogeneous group of protein misfolding diseases characterized by extracellular deposition in organs and tissues of amyloid fibers, leading to severe organ dysfunction and death. Systemic amyloidosis often involves multiple organs. Heart and kidney are the most commonly affected organs, whereas skeletal muscle involvement is rare and often accompanied by other organs’ involvement. Case Summary We reported a 70-year-old man manifested with myopathy followed by heart failure who was suspected of transthyretin amyloidosis clinically, after the pathological results and the 99mTc-pyrophosphate (99mTc-PYP) scintigraphy, light-chain (AL) amyloidosis involving the heart and skeletal muscle was confirmed. Conclusion The patient’s unique presentation gives insight into a rare but debilitating disorder and the potential link between various types of amyloidosis. In addition, myopathy in amyloidosis should be recognized.